Analysis of the relationship between treatment patterns based on patient characteristics in cases of hypertension complications at PKU Muhammadiyah Gamping Hospital - Ariansyah, Diffa Zahra; Wulandari, Ari Susiana; Estiningsih, Daru; Nurinda, Eva (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background   : Hypertensive disease is often referred to as "The Silent Disease" or silent disease. The percentage of complication hypertension in Indonesia is cerebrovascular disease 21.6%, heart disease 40.9%, and kidney disease 33.2%. Yogyakarta is one of the provinces in Indonesia with a prevalence of complication hypertension of 32.86%. Each year, an estimated 9.4 million people die from hypertension and complications.Objective        : To analyze the relationship between treatment patterns based on sociodemographic characteristics in complication hypertensive patients in Inpatient PKU Muhammadiyah Gamping Hospital.Methods: This study was analytical research methods using retrospective methods. The sampling technique was in this study is the total sampling technique. The variables used in this study were patterns of antihypertensive drug use associated with sociodemographic factors including gender, age, and patient health insurance (BPJS or non-BPJS). The test analysis was Chi-Square Test and Kendall's tau-b Test for variable blood pressure relationships and drug use patterns.Results: Sociodemographic characteristics of respondents include: adult age (16.7%) and elderly (83.3%), male and female gender (50.0%), BPJS treatment coverage (91.7%) and general (8.3%). Hypertensive disease complications include: stroke (20.8%), myocardial infarction (4.2%), kidney failure (4.2%), heart failure (33.3%), diabetes mellitus (37.5%). Drugs used: Amlodipine (23.10%), Candesartan (30.80%), Nifedipine (11.50%), Bisoprolol (19.20%), Clonidin (5.80%), Captopril (1.90%), Lisinopril (3.80%), and Ramipril (3.80%).Conclusion: There was no relationship between sociodemographic characteristics and treatment patterns and there was a relationship between systolic / diastolic blood pressure with drug use patterns in cases of complication hypertension at PKU Muhammadiyah Gamping Hospital.